Caractériser les trajectoires de jeunes de quartiers populaires : une analyse par les récits de soi - Jeanne Demoulin; Leïla Frouillou; Collectif Pop-Part (Sociétés et Jeunesses en Difficulté, 2022)
This paper results from a recent collective participatory research project (ANR Pop-Part 2017-21). It focuses on the trajectories of young people from working-class neighbourhoods in Ile-de-France. Media and even sociological views often polarize on two complementary figures in the educational pathways of young working-class people the rarity of exceptional trajectories doubles the number of failures and difficulties. On the contrary, the aim here is to highlight the heterogeneity of social and educational trajectories in working-class neighbourhoods. They are concerned by the general increasing complexity in the transition to adulthood. We examine the socially situated ways in which young people describe their lives. Understanding the heterogeneity of trajectories implies a detailed approach to social positions, crossing social origin, family configurations, gender and sexuality, as well as inter-generational migration trajectories and religious practices. The first part presents four ideal-typical ways of telling one’s story in an interview, illustrated by several portraits, which make it possible to bring out contradictions in the story, and proximities or porosities between the narratives. The second part shows the differences in position in the social space between these young people, in order to grasp the effects on their relationship to the world.